Isolated Central Nervous System Vasculitis Associated with Antiribonuclear Protein Antibody - Amer M. Awad; Mathew Stevenson (Case Reports in Neurological Medicine)
We describe the case of a young woman who was referred to a tertiary care center with unexplained subacute progressive encephalopathy preceded by long-standing severe headaches. Her extensive workup was remarkable for abnormal intracranial angiography suggestive of small- and medium-vessel vasculitis, persistently elevated protein in the cerebrospinal fluid and persistently high titers of antiribonuclear protein antibody. The patient showed a modest response to intravenous high-dose steroids. We propose that the patient's neurologic disease is secondary to immune-mediated central nervous system vasculitis, possibly as an initial manifestation of mixed connective tissue disease.